Research on Optimization of Association Rules Mining Algorithm. Issue 4 (August 2019) - Li, Ningning; Lu, Zhaoxia
Abstract: The association rules mining algorithm is always one of the specialists most concerned topics in the research of database knowledge. It is widely used in many fields in society. This article is based on association rule mining algorithm to put forward the relevant strategies for the majorization to make the mining algorithm get better application. With the development of the society, social information becomes richer and richer, people also become more and more interested in the unknown world. Sustainably improve the automation and intelligentization of the tools for processing information can continually improve the abilities in many ways and get more useful information from the huge database. So the appearance of the data mining makes it possible. It can fetch some hidden, unknown and useful information and knowledge from the huge practical application data. And the association rule is a main mode in research of data mining. It can fetch target data by finding the dependency between fields of a given condition from different data fields. As a result, the optimization of association rules mining algorithm is of quite importance in fetching target data.